TINJAUAN YURIDIS PENANDATANGANAN PERJANJIAN DI RUMAH TAHANAN - Hartati, R. AY. Sri (E-Journal Widya Yustisia, 2005)
Contract Law embraces an open system meaning provides freedom to all parties to make an agreement as long as it does not infringe public ans decency, In contract law the freedom of contract is according to Chapter 1338 article (1) Commercial law book meaning agreement is legal serving as law for parties in contract. For an agreement to be legal requires conditions as stated in chapter 1320 Commercial law book namely parties in agreement, caoability in making agreement, other conditions, and authenticity. Agreement means free agreement not under pressure, unknowing, and deception will cause agreement cancellation. Agreement by unlawful force on imprisoned individual is cancelled by Law